(3JGQjN CSeGA GdKbGJ eef fbd Yfge GdYdes - (3CHh MaU YeQ Hf CMeO Hf YKeGf Hf TGgjf,J (B385 (3g` s
(3ChdgG (B:s
(3CNHQfG GdMejOi Yf CHj MaU bGd (B: (3cJGH CSeGA GdKbGJ eef Qhi GdMOjK eef GfJgi EdjfG PcQg Yf fbGO GdMOjK eef bHdJ TgGOJg s
(3BNQgG (B:s
(3ef HGH GdjGA , bhdg (B: (3abGd dg CMeO GScJ gh jYQa NWC GdMOjK bGd cGf jbGd NPhG GdMOjK fe GdKbGJ BNQ cJGH JGQjN CSeGA GdKbGJ eef fbd Yfg GdYde GdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3eQJH Ydi MQha GdeYLes
(3cJHJ Hbde eVHhW hHBNQgG KdGK hQbGJ efaQOGJ dYdgG ef GdfSNIs
(3UhQJ Yf fSNI HOGQ GdcJH GdeUQjI hQbegG (B99 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B40s
Keywords: (3GdJGQjNs